The repertory grid technique as a method for the study of cultural differences - Tomico, Oscar; Karapanos, Evangelos; Lévy, Pierre; Mizutani, Nanami; Yamanaka, Toshimasa (My University, 2009)
Culture is typically approached in the field of design through generic, cross-domain constructs. In this paper we provide an alternative methodological approach to exploring cross-cultural differences by studying the idiosyncratic views of individuals with regard to existing products. We operationalize this approach through the Repertory Grid Technique, a structured interview technique motivated by Kelly's Personal Construct Theory, and propose a content-analytic procedure combining quantitative and qualitative information. We further propose the use of three distinct metrics in the analysis of personal constructs: dominance, importance, and descriptive richness. Dominance of a construct is measured through the relative percentage of a construct category over the total sample of constructs. Importance is measured through the elicitation order; this assumes that constructs elicited first are more salient and important to the individual. Descriptive richness relates to the diversity of a class of constructs. Some constructs might be uni-dimensional while others might tap to a number of distinct facets. The use of these indices enables the quantification of the different ways in which individuals perceive and differentiate between products. By identifying how individuals respond to a rich set of stimuli within a given domain, we inquire into their values and the qualities they appreciate within this restricted domain. Cultural values are thus explored in relation to a set of stimuli. We tested this procedure through an exploration of the ways 17 Dutch and 16 Japanese industrial designers valued a set of pens.
Keywords: Repertory Grid; Cultural Differences; Designers’ Perceptions; Product Attribute Prioritization Measurements